Fabrication of high-quality GaN substrates using the Na flux method. (31st March 2016) - Maruyama, Mihoko; Nakamura, Koshi; Che, Songbek; Murakami, Kosuke; Takazawa, Hideo; Imanishi, Masayuki; Imade, Mamoru; Morita, Yukihiro; Mori, Yusuke
Abstract: Gallium nitride (GaN) substrates fabricated along the nonpolar and semipolar directions are the most promising materials for realizing optical and electronic devices with low power consumption. In this study, we carry out the Na flux growth on -plane GaN templates grown heteroepitaxially on sapphires. The GaN crystals are grown at low supersaturation using the Na flux method with the dipping technique. The crystallinity of the grown GaN crystals is improved compared to that of the seed substrates. Then it improves further by lowering the supersaturation. Finally, we succeed in fabricating a 2-in. -plane GaN single crystal with high transparency and crystallinity.